2018
DOI: 10.15171/hpp.2018.17
|View full text |Cite
|
Sign up to set email alerts
|

Dietary patterns and risk of prostate cancer: a factor analysis study in a sample of Iranian men

Abstract: Background: Prostate cancer is one of the most common types of cancer with a high mortality rate. The current study was conducted to investigate the relationship between dietary patterns and prostate cancer risk among Iranian men.Methods: This case-control study was conducted in Kermanshah province in western Iran in November 2016. Fifty patients with prostate cancer were selected as cases and 150 healthy men matched for age and body mass index (BMI) were selected as controls. Dietary intake data were collecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 33 publications
1
18
0
Order By: Relevance
“…However, high BMI participants of European American origin had a tendency of demonstrating risk to PCa development (Pichardo, Smith, Dorsey, Loffredo, & Ambs, ). On the contrary, Bagheri et al examining dietary patterns and the risk of PCa demonstrated that BMI was not associated with PCa risk among Iranian men, but an unhealthy dietary pattern was (Bagheri et al, ).…”
Section: Discussionmentioning
confidence: 98%
“…However, high BMI participants of European American origin had a tendency of demonstrating risk to PCa development (Pichardo, Smith, Dorsey, Loffredo, & Ambs, ). On the contrary, Bagheri et al examining dietary patterns and the risk of PCa demonstrated that BMI was not associated with PCa risk among Iranian men, but an unhealthy dietary pattern was (Bagheri et al, ).…”
Section: Discussionmentioning
confidence: 98%
“…This difference can be mainly due to population-based prostate cancer screening and use of advanced diagnostic methods (PSA testing and TURP) which are expanding in most developed countries, whereas they have not been widely taken into consideration in developing communities. 22-24 Hence, it is predictable that number of new cases will increase by earlier detection of the cancer in western nations more than in the eastern nations.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on dietary patterns have reported that high healthy eating index (HEI) or adherence to Mediterranean diet characterized by fruits, grain, vegetable, and nuts are associated with lower risk of prostate cancer (Bosire et al, 2013;Möller et al, 2013;Hashemian et al, 2015;Eslamparast et al, 2017). By contrast, unhealthy dietary patterns like western diet, where red and processed meat and saturated fatty acids are highly consumed, are associated with higher risk of prostate cancer (Askari et al, 2014;Bagheri et al, 2018).…”
Section: Introductionmentioning
confidence: 99%